The effect of mothers' empowerment program on premature infants' weight gain and duration of hospitalization - Fatemeh Mohammaddoost; Ziba Mosayebi; Hamid Peyrovi; Minoo-Mitra Chehrzad; Abbas Mehran (Wolters Kluwer Medknow Publications, 2016)
Background: The readiness of mothers to take care for infants at discharge is a critical issue. Poor readiness of mothers in taking care of premature infants at the time of discharge is associated with potential adverse consequences. This study examined the effect of implementing mothers' empowerment program on the weight gain and duration of hospitalization in premature infants. Materials and Methods: This study was a quasi-experimental before-after study with a control group, in which 80 mothers with premature infants who were hospitalized in NICU Level II of two hospitals were recruited in the study. Mothers' empowerment program was implemented as a three-stage training program for the intervention group. Mothers' readiness questionnaire was completed by the mothers before the intervention and at the discharge time. The changes in mean of mothers' readiness scores were compared in both the groups. Results: The mean of daily weight gain in infants of the intervention group (3.95 g) was significantly higher than that of the infants in the control group (−0.9 g) (P = 0.003). The average duration of hospitalization for infants in the intervention and control groups was 15.45 days and 20.95 days, respectively, showing a statistically significant difference (P = 0.003). Conclusions: Providing training to the mothers regarding how to care for premature infants can be a useful and effective method in the process of weight gain of premature and low-birth newborns, and may shorten the duration of infants' hospitalization.